PEMANFAATAN KITOSAN UNTUK PENGENDALIAN BEAN COMMON MOSAIC VIRUS (BCMV) PADA KACANG PANJANG - Tri Asmira Damayanti; . Haryanto; Suryo Wiyono (Universitas Lampung, 2013)
Utilization of chitosan to control Bean common mosaic virus (BCMV) on yard long bean. Bean common mosaic virus (BCMV) is one of important viruses infecting yard long bean in Indonesia. One of efforts to control its infection is by utilizing chitosan. Thus, the aim of the conducted research was to test the effectiveness of chitosan in controlling BCMV on yard long bean. Concentration of chitosan tested were 0.1% and 1.0% and it was applied as seed treatment (PB), leaf spraying before (SB) and after (ST) mechanical inoculation of BCMV. Incubation period, disease incidence and severity, peroxidase enzyme activity, and BCMV titer were measured as observation parameters. Incubation period of all treated plants were longer as compared with untreated control plants. Symptoms of treated plants at concentration 0.1% (SB and ST) showed mild to severe symptom and leaf malformation, while at concentration 1.0% showing milder symptoms and some of tested plants remain symptomless. Treated plants showed lower peroxidase enzyme activity and significantly lower BCMV titer as compared with that of untreated control plants. The lowest to highest percentage of virus inhibition exhibited by ST0.1, SB0.1, PB0.1, PB1, SB1 and ST1 treatments with virus relative inhibition level ranged 75.94%-86.07% and severity inhibition level ranged 39.55%-64.63%.